2016
DOI: 10.1371/journal.pone.0168478
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Bus Networks in India

Abstract: In this paper, we model the bus networks of six major Indian cities as graphs in L-space, and evaluate their various statistical properties. While airline and railway networks have been extensively studied, a comprehensive study on the structure and growth of bus networks is lacking. In India, where bus transport plays an important role in day-to-day commutation, it is of significant interest to analyze its topological structure and answer basic questions on its evolution, growth, robustness and resiliency. Al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 37 publications
(63 reference statements)
0
17
0
Order By: Relevance
“…Small world property is an important characteristic in complex network theory, which indicates that any two nodes in a network can be accessed by a few number of links. In general, a small world network is characterized by a high clustering coefficient and a small shortest path length [41][42][43]. It is demonstrated that all scale-free networks are believed to display small-world properties [22].…”
Section: Small World Networkmentioning
confidence: 99%
“…Small world property is an important characteristic in complex network theory, which indicates that any two nodes in a network can be accessed by a few number of links. In general, a small world network is characterized by a high clustering coefficient and a small shortest path length [41][42][43]. It is demonstrated that all scale-free networks are believed to display small-world properties [22].…”
Section: Small World Networkmentioning
confidence: 99%
“…We see evidence of this in natural systems everywhere, from cardiovascular networks to cities [5,14]. In many such systems the scaling laws, which are generally power-law relations, f (y) ∼ y δ , define the scale-free properties of change, with δ being the scaling exponent [15,16,17,18]. Due to the presence of scaling relationships and powerlaw decays in the statistical properties of the networks, the importance of the respective nodes is non-uniform.…”
Section: Introductionmentioning
confidence: 99%
“…e preferential attachment can be observed everywhere and can be applied in the urban traffic networks modelling as normally for the representation method of dual approach. Many researches have shown that traffic networks are typically and theoretically scale-free [35,50,51] with dual approach rather than primal approach, with power-law distribution in log-log plot, and the degree distribution exponent has large effects on the performances of traffic network, and the distribution of urban traffic flows also following scale-free properties [52,53]. Zhang [54] proved that 50 extracted dual urban traffic networks of USA are following scale-free properties, and Kalapala et al [55] found that, with the dual representation, the degree distribution of the urban street networks can better fit with the power-law functions with…”
Section: Barabasi-albertmentioning
confidence: 99%